Updates on Molecular Targeted Therapies for CNS Tumors - Pan, Edward (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The challenges in identifying effective therapies for CNS tumors continue to be daunting. Potentially effective targeted therapies must be able to penetrate the blood-brain barrier to reach the tumor and, in sufficient concentrations, to result in meaningful treatment responses. Moreover, molecular targets must be key drivers in the growth and progression of CNS tumors. Numerous potentially efficacious therapies have failed in randomized clinical trials due to other factors, including subclonal genetic intratumoral heterogeneity (particularly within malignant gliomas), epigenetic heterogeneity, and failure to target important factors involved in the tumor microenvironment. Developing effective targeted therapies requires a thorough fundamental understanding of the genetic and epigenetic factors driving tumor progression, the interactions between CNS tumor cells and the tumor microenvironment, and the key mechanisms of tumor treatment resistance. In this Special Issue, experts in the field of CNS tumors will highlight the most promising molecular targets in the development of treatments for patients with CNS tumors.